2019
DOI: 10.5897/jat2018.0329
|View full text |Cite
|
Sign up to set email alerts
|

Operational efficiency and financial sustainability of listed manufacturing companies in Nigeria

Abstract: This study investigates the impact of operational efficiency on the financial sustainability of listed manufacturing companies in Nigeria. The recent economic crisis in Nigeria has caused an alarming decline in financial sustainability indicators of manufacturing companies. Managers are forced to make efficient use of resources to maximize profitability so as to cope with and compete in the harsh economic condition. Several measures of efficiency were analysed in relation to financial sustainability. There is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 37 publications
4
16
0
1
Order By: Relevance
“…They tested a sample of 1,357 Portuguese firms and concluded that firms that downsize largely maintain their underperformance compared to those that do not downsize. This result is similar with that of Imhanzenobe (2019) who discovered that changes in number of employees had no significant impact on the financial sustainability position of companies. Carriger (2018) also did a study that investigated the effectiveness of downsizing.…”
Section: Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…They tested a sample of 1,357 Portuguese firms and concluded that firms that downsize largely maintain their underperformance compared to those that do not downsize. This result is similar with that of Imhanzenobe (2019) who discovered that changes in number of employees had no significant impact on the financial sustainability position of companies. Carriger (2018) also did a study that investigated the effectiveness of downsizing.…”
Section: Methodssupporting
confidence: 89%
“…Challenges like changes in organizational culture and value, lack of actualization of predicted synergy and top management turnover ought to be managed with caution as these could also have significant effects on the successful implementation of such strategies (Cording, Christmann and King, 2008). Some authors identified a positive impact of restructuring strategies on firms' competitive advantage and overall financial performance (Robbins and Pearce, 1992;Chowdhury and Lang, 1996;Sudarsanam and Lai, 2001;Boyne, 2004) while some others identified a negative impact (Sudarsanam and Lai, 2001;Imhanzenobe, 2019). A potential explanation for this discrepancy is that some authors investigate restructuring as an isolated strategy, whereas others investigated it as the first stage in the process of a turnaround strategy (Arogyaswamy et al, 1995).…”
Section: Finding and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, it is found that TAT had significant and positive influence on ROA in both Malaysia and Indonesia F&B industry where it supports the result of research done by Imhanzenobe (2019) which stated that asset turnover had significant and positive influence on company's performance. It potentially determines and is indicating that a good asset turnover of a company is efficiently and optimally able to earn more company's income through favorable increase of company's sales volume based on the utilization of the company's assets.…”
Section: Finding and Discussionsupporting
confidence: 74%
“…The impact of operational efficiency on the financial sustainability of the manufacturing companies listed in Nigeria was investigated by Osazefua (2019). Nigeria's recent economic crisis has caused an alarming decline in manufacturing companies ' financial sustainability indicators.…”
Section: Literature Reviewmentioning
confidence: 99%